Impact of sex hormones on postoperative outcomes in plastic surgery: a narrative review - Lv, Xiong; Xiang, Chun; Zheng, Yan; Lv, Xuling; Zhou, Wanxuan; Zhu, Jiajun (Frontiers in Surgery, 2025)
BackgroundSince 1929, when scientists first identified estrogen in urine and coined the term “sex hormones,” these vital steroid hormones have been recognized for their critical role in tissue repair and wound healing. This is particularly evident in the postoperative recovery of plastic surgery patients. While the effects of sex hormones differ between males and females, their mechanisms in wound healing, angiogenesis, and collagen regulation have drawn significant attention.MethodsThis narrative review synthesizes key literature from four databases including PubMed (up to 2024) focusing on the effects of sex hormones on healing after plastic surgery.Key terms such as “sex hormones,” “tissue repair,” and “postoperative recovery” were used. The analysis highlights the differential roles of estrogen and testosterone in skin healing, angiogenesis, and inflammatory responses. Additionally, it explores the effects of sex, age, and hormone replacement therapy (HRT) in transgender patients on surgical outcomes.The main target audience of this article is professional surgeons and endocrinologists, medical students and scientific researchers.ResultsExisting evidence suggests that estrogen enhances wound healing by upregulating vascular endothelial growth factor (VEGF), stimulating angiogenesis, and playing a pivotal role in collagen regulation. Testosterone may influence fibroblast proliferation and angiogenesis, although its effects vary by sex and age. Postmenopausal women exhibit diminished healing capacity due to decreased estrogen levels, whereas transgender patients undergoing HRT show improved postoperative recovery.ConclusionSex hormones significantly influence postoperative recovery in plastic surgery. The distinct mechanisms of estrogen and testosterone in wound healing provide valuable insights for personalized medical approaches, optimizing surgical outcomes across diverse patient populations.